Negotiating Meanings of Borderlands in relation to Arabness, Americanness and Muslimness: Mohja Kahf’s The Girl in the Tangerine Scarf (2006) - Dalal Sarnou (Transatlantica)
Anglophone Arab writings have come of age after years of ethnic, religious and gender-based invisibility. This literature has carved out a niche for itself as a literature of minority, of womanhood and of borderlands. Recent theorizations on borderland zone(s) have endeavored to understand journeys of displacement and dislocation that immigrants may experience. The present paper offers an investigation of how the border zone, be it geographical or psychological, is fictionalized in Arab Anglophone women narratives. The novel of the Arab American Mohja Kahf, The Girl in the Tangerine Scarf (2006), highlights the borderland zone occupied by Arabs in the diaspora and represented by Khadra, the novel’s protagonist. Kahf’s novel serves here as a case study that shows how women characters have to negotiate their Arabness, Americanness and Islamness. The question is how.